(untitled) (Journal of Computational Mathematics, 2007)
In this paper, two new nonconforming hexagonal elements are presented, which are based on the trilinear function space Q_1^(3) and are edge-oriented, analogical to the case of the rotated Q_1 quadrilateral element. A priori error estimates are given to show that the new elements achieve first-order accuracy in the energy norm and second-order accuracy in the L^2 norm. This theoretical result is confirmed by the numerical tests.